1977
DOI: 10.1104/pp.60.5.693
|View full text |Cite
|
Sign up to set email alerts
|

pH Dependence of Photosynthesis and Photorespiration in Soybean Leaf Cells

Abstract: The processes of photosynthesis and photorespiration are linked together by the carboxylase and oxygenase activities of RuDP2 carboxylase, and the relative rates of these processes can be expressed in terms of the kinetic properties of RuDP carboxylase with respect to the two mutually competitive substrates CO2 and 02 (7,8,10). In this analysis, the rate of photorespiration relative to photosynthesis is given by the equation:Photorespiration/photosynthesis = tv0Iv, = tV0K,O/VIKV C (1) where v. and v, are the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 15 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…Servaites and Ogren (22) attributed the increased apparent affinity which they observed in their soybean cell system to increased affinity of RuBP carboxylase for CO2. That a change in internal pH of sufficient magnitude to bring about the required change in the Km (C02) of RuBP carboxylase (22) can wholly explain our own findings seems unlikely for the following considerations. First, our observations suggest that overall internal pH rose relatively slightly with rising external pH, and other investigators using a variety of techniques have reported that the internal change is even smaller (25).…”
Section: Discussionmentioning
confidence: 76%
“…Servaites and Ogren (22) attributed the increased apparent affinity which they observed in their soybean cell system to increased affinity of RuBP carboxylase for CO2. That a change in internal pH of sufficient magnitude to bring about the required change in the Km (C02) of RuBP carboxylase (22) can wholly explain our own findings seems unlikely for the following considerations. First, our observations suggest that overall internal pH rose relatively slightly with rising external pH, and other investigators using a variety of techniques have reported that the internal change is even smaller (25).…”
Section: Discussionmentioning
confidence: 76%
“…As a result algae have C4-like photosynthetic characteristics such as very low r (CO2) and r (DIC) values (5, 18), r shows little or no sensitivity to 02 and temperature (5,8,18), there is little apparent 02 inhibition of photosynthesis (8,18) and photorespiration is minimal or absent (6,18). The intervention of a HCO3 transport mechanism, presumably located at the plasmalemma, of Coccochloris peniocystis and Anabaena variabilis has a profound effect on the kinetics of whole-cell photosynthesis (3,8) (25) indicated that K1/2 (CO2), r (CO2) and the magnitude of 02 inhibition of photosynthesis decreased with increasing pH. However, in these experiments CO2 equilibration between the aqueous and gaseous phases in the reaction vials was not taken into account (23).…”
Section: Resultsmentioning
confidence: 90%
“…After 60 min incubation in the presence of 33 nm SO2, the decrease of the pH of the cytoplasm was calculated from known buffering capacities (27,28) to be about 0.7 pH units. In the chloroplast stroma, such a decrease should inhibit photosynthesis by inhibiting fructose bisphosphatase and sedoheptulose bisphosphatase (4,6,7,30,33,38). At an SO2 concentration of 82 nm ( Fig.…”
mentioning
confidence: 99%